Theoretical and methodological foundations of pedagogical interaction of the educational process participants - Gonchar O.V (Kharkov National Pedagogical University, 2010)
Theoretical and methodological foundations of pedagogical interaction of the educational process participants at the system of higher school in the XX century are investigated. At the modern stage of pedagogical theory and humanization of higher education development it becomes aware of the burning necessity of reconsideration of historical inheritance of pedagogical knowledge about pedagogical interaction of a teacher and students. But research of any phenomenon couldn't be perfect and qualitative without understanding of philosophy and logic of its formation.